2002
DOI: 10.1086/342577
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of a Citywide Outbreak of Extended‐Spectrum β‐Lactamase–ProducingKlebsiella pneumoniaeInfection

Abstract: Multidrug-resistant strains of Klebsiella pneumoniae are a problem in many hospitals. In 1999, the molecular epidemiology of K. pneumoniae with extended-spectrum beta-lactamases (ESBLs) was studied at 15 hospitals in Brooklyn. Of 824 unique patient isolates, 34% were presumptive ESBL producers. Of this subset, 34% were susceptible to cefoxitin, 42% to ciprofloxacin, 48% to ceftriaxone, 55% to piperacillin-tazobactam, 57% to amikacin, and 86% to cefepime. Ribotype analysis revealed 87 unique types. However, 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 30 publications
4
49
0
5
Order By: Relevance
“…Nicolle et al 13 found that in their CIC patients the most often isolated febrile UTI-causative bacteria were E. coli (35%), followed by K. pneumonia (26%), P. aeruginosa (23%) and Proteus mirabilis (16%). The major difference is the rate of K. pneumonia isolation and there is a different trend of the rate of ESBL production: for instance, ESBL-producing bacteria are reported in Japan at a rate of 1.3-6.7%, similar to our data (0%), 14,15 but a much higher rate in the United States (34%) 16 and Turkey (33%). 17 Regarding antibiotic-resistant bacteria, Chong et al 18 found that 14.3% of all E. coli isolates in UTI were ESBL producers, whereas other studies reported 21.0% in CAUTI and found indwelling urethral catheterization was a risk factor for ESBL production.…”
Section: Discussionsupporting
confidence: 78%
“…Nicolle et al 13 found that in their CIC patients the most often isolated febrile UTI-causative bacteria were E. coli (35%), followed by K. pneumonia (26%), P. aeruginosa (23%) and Proteus mirabilis (16%). The major difference is the rate of K. pneumonia isolation and there is a different trend of the rate of ESBL production: for instance, ESBL-producing bacteria are reported in Japan at a rate of 1.3-6.7%, similar to our data (0%), 14,15 but a much higher rate in the United States (34%) 16 and Turkey (33%). 17 Regarding antibiotic-resistant bacteria, Chong et al 18 found that 14.3% of all E. coli isolates in UTI were ESBL producers, whereas other studies reported 21.0% in CAUTI and found indwelling urethral catheterization was a risk factor for ESBL production.…”
Section: Discussionsupporting
confidence: 78%
“…However, because of the instability of many ␤-lactams in culture media, no such media exist for the detection of resistant gram-negative pathogens. The difficulty of screening fecal surveillance cultures for bacteria with ESBLs has undoubtedly been an impediment in our efforts to control the spread of these pathogens in the New York City region (15).…”
Section: Discussionmentioning
confidence: 99%
“…Por el contrario, varios estudios han examinado la asociación entre antimicrobianos y la producción de BLEE. La mayoría indica como la clase de antimicrobiano más importante asociada a la producción de BLEE a las cefalosporinas de tercera generación 21,22 . Esta asociación ha sido representada más claramente en los estudios de intervención dirigidos a reducir el uso de cefalosporinas, derivando en la reducción de la incidencia de K. pneumoniae productora de BLEE 14,17 .…”
Section: Síntesisunclassified